Aumento del diámetro ecográfico coledociano y colecistectomía parcial como factores de riesgo para coledocolitiasis residual - García Rodríguez, Frank Stuart (2019)
OBJECTIVE: Determine if the increase of the coledocian echographic diameter and partial cholecystectomy are risk factors associated with residual choledocholithiasis in patients treated at the Belen’s Hospital of Trujillo. METHODOLOGY: A retrospective case-control study was carried out. For the cases, 63 clinical records of cholecystectomized patients with residual choledocholithiasis of the HBT were evaluated during the period January 2010 - December 2015. For the controls, the same number of patient histories without residual choledocholithiasis was taken. Frequencies of presentation of the echocardiographic diameter> 10 mm and partial cholecystectomy were calculated for both groups, and were compared using the Z test, considering a level of significance of 0.05. RESULTS: Fifty patients with an echocardiographic diameter> 10mm who developed residual choledocholithiasis were found. In addition, 76 with diameter <10 mm of which 30 developed the disease under study. Likewise, 18 of 27 patients presented partial colicistectomy and developed CR, 99 did not present partial cholecystectomy and 45 developed the disease. A statistically significant association was found between increase of the echocardiographic diameter, partial cholecystectomy and residual choledocholithiasis with odds ratio of 2.98 and 2.4 respectively and 95% confidence interval. CONCLUSION: Cholechocyte ultrasound diameter> 10 mm and partial cholecystectomy are risk factors for residual choledocholithiasis.